THE CORRELATION BETWEEN NUTRITIONAL STATUS AND CALCIUM ADEQUACE LEVEL ON THE INCIDENCE OF PREMENSTRUAL SYNDROME (PMS) IN FEMALE STUDENTS AT THE FACULTY OF PUBLIC HEALTH UNIVERSITAS AIRLANGGA - Lailatul Masruroh; Lailatul Muniroh (Universitas Airlangga, 2021)
ABSTRACTPremenstrual syndrome (PMS) is a series of symptoms consisting of physical symptoms, emotional symptoms, and behavioral symptoms experienced by women before menstruation. PMS is caused by several factors, including nutritional status and calcium intake. This study was conducted to analyze the correlation between nutritional status and adequacy levels of calcium with the incidence of PMS in female students at the Faculty of Public Health, Universitas Airlangga. This research used a cross sectional design. The sample consisted of 83 female students at the Faculty of Public Health, Airlangga University class of 2015-2017, chosen through simple random sampling. Data and methods used in the study included measurements of body weight and height to get nutritional status variable, the food recall 2x24 hours form to record adequacy levels of the calcium variable, and the Shortened Premenstrual Assessment Form (SPAF) questionnaire to get incidence of the PMS variable. Data were analyzed using the Chi-square test. The results of statistical tests showed that there was a correlation between nutritional status (p = 0.012) and PMS, but there was no correlation between calcium intake (p = 0.878) and the incidence of PMS. The conclusion of this study is women were overweight were more likely to experience more severe PMS and women who had low calcium did not experience notable patterns in their incidence or severity of PMS. Keywords: nutritional status, calcium, premenstrual syndrome